The Extraction of Oxalate Acid from Porang Flour (Amorphophallus oncophyllus) using Microwave-Assisted Solvent Extraction - Ansori, Ansori; Kusuma, Heri Septya; Maula, Fikaputri Rohmatul; Qadariyah, Lailatul; Mahfud, Mahfud (Syarif Hidayatullah State Islamic University, 2023)
Porang (Amorphophallus oncophyllus) is one of the local annual plants that contain high levels of oxalate. Oxalates are undesirable compounds in porang flour, and their levels must be removed or reduced to obtain high quality porang flour as a food ingredient. In this research, the extraction of oxalate acid was conducted using microwave-assisted solvent extraction and mechanical separation methods. This study aims to analysis the parameters that influence the extraction of oxalate acid using microwave-assisted solvent extraction such as the effect of microwave power, extraction time, feed-to-solvent ratio (F/S) and material size. The mechanical separation process will be studied the effect of material size for extraction of oxalate acid. The optimum yield obtained for oxalate acid extraction with microwave-assisted solvent extraction was microwave power of 600 W, extraction time of 30 min, feed-to-solvent ratio of 0.05 g/mL and porang size of 100 mesh obtained by oxalate acid yield of 24.78%. Porang size of 100 mesh was the optimum yield obtained for extraction of oxalate acid using mechanical separation method. The result of physical properties test using SEM-EDX and FTIR shows that extraction of oxalate acid from porang using microwave extraction method could produce oxalic acid which has good quality. In addition, extraction using microwave offers an environment-friendly extraction method, which can accelerate and increase the oxalate acid extraction yield.